A philosophical framework for a general education program of a university - Acoymo, Ramon Ma (2005)
A review of the history of General Education (GE) at the University of the Philippines revealed that the scope, latitude, breadth and depth of the literature, rhetoric, and argumentation pertaining to and surrounding the concept generated an unwieldy conglomeration of ideas, observations and information which did not provide objectivity and consistency of context or perspective. A framework constructed upon the aspects and skills of Philosophy shall provide the objectivity and consistency of context and perspective. Definition of terms central to the issues, questions and problems of the GE, critiques on selected university programs of GE, a criteria upon which to base the formulation of programs of GE, major Philosophies of Education's perspectives that will discern a philosophy most appropriate to guide and assess GE, and recommendations of courses of action based upon the objective and consistent context and perspective provided by philosophy, were contained in this framework.